EVALUASI KEBIJAKAN PENGELOLAAN SAMPAH - Novalita, Perdana; Heriyanto, Meyzi; Muchid, Muchid (Jurnal Ilmu Administrasi Negara, 2018)
Evaluation of Waste Management Policy. This study aims to find out and analyze the evaluation of waste management policy in Kecamatan Tampan Pekanbaru City. The type of this research is descriptive research. The research informants are Camat, RT, officers and community. Data collection techniques used in this study is to use interviews, documentation and observation. The results showed that after evaluation of waste management policy in Kecamatan Tampan Pekanbaru was good enough, although there are still shortages here, such as the socialization of waste management policies to the community, the provision of hygiene facilities and public awareness issues to protect the environment.